2021
DOI: 10.1002/gcc.22933
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid cohesion defects are associated with chromosomal copy number heterogeneity in high hyperdiploid childhood acute lymphoblastic leukemia

Abstract: High hyperdiploid acute lymphoblastic leukemia (ALL) is one of the most common malignancies in children. The main driver event of this disease is a nonrandom aneuploidy consisting of gains of whole chromosomes but without overt evidence of chromosomal instability (CIN). Here, we investigated the frequency and severity of defective sister chromatid cohesion—a phenomenon related to CIN—in primary pediatric ALL. We found that a large proportion (86%) of hyperdiploid cases displayed aberrant cohesion, frequently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…To investigate whether the observed differences in heterogeneity were due to mutations in genes affecting genomic stability, we screened bulk WGS data, but no such correlation was seen (Supplementary Table 1 ). We further investigated whether increased heterogeneity correlated with the presence of sister chromatid cohesion defects in metaphase chromosomes, which we have recently reported to be associated with increased chromosomal heterogeneity in HeH ALL 14 . Indeed, #2, which had the second highest heterogeneity score, had a very high frequency of cohesion defects in metaphase cells (85%; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether the observed differences in heterogeneity were due to mutations in genes affecting genomic stability, we screened bulk WGS data, but no such correlation was seen (Supplementary Table 1 ). We further investigated whether increased heterogeneity correlated with the presence of sister chromatid cohesion defects in metaphase chromosomes, which we have recently reported to be associated with increased chromosomal heterogeneity in HeH ALL 14 . Indeed, #2, which had the second highest heterogeneity score, had a very high frequency of cohesion defects in metaphase cells (85%; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the potential contribution of condensin complex and spindle assembly checkpoint impairments, Molina et al found that inhibition of the Aurora B kinase and the spindle assembly checkpoint produced substantial chromosomal instability in healthy CD34-positive hematopoietic cells, the outcome of which were indeed aneuploid cells with chromosomes that displayed ALL-typical structural and condensation defects (Molina et al, 2020). In support of these findings, Moura-Castro et al (2020) also observed similar severe cohesion defects in a large proportion of hyperdiploid cases, especially in those with an increased copy number heterogeneity. Nevertheless, even if one concedes that these observations are highly relevant, it still remains unclear what actually would trigger these disturbances in the first place.…”
Section: Formation Of Uneven Ploidy Patternsmentioning
confidence: 95%
“…Studies on mosaicism detection in cancer mainly used BAFSegmentation, TAPS, PICNIC, GISTIC and CNAG relating acute myeloid leukemia [ 234 ], hyperdiploid childhood acute lymphoblastic leukemia [ 235 ], ossification of fibromyxoid tumors [ 236 ], gastric adenocarcinoma [ 237 ], hepatoblastoma [ 238 ], lymphoblastic leukemia [ 239 ] and non-Hodgkin B-cell lymphoma [ 240 ]. Also, mosaicism genotyping was performed with MoChA, MAD, BAFSegmentation and PICNICfor mastocytosis [ 241 ] and drug resistance.…”
Section: Recent Studies Applying Inference Methods Of Snp Datamentioning
confidence: 99%